Detection of JC Virus DNA in Human Tonsil Tissue: Evidence for Site of Initial Viral Infection - Monaco, Maria Chiara G. (American Society for Microbiology, 1998)
Progressive multifocal leukoencephalopathy is a demyelinating disease of the human central nervous system that results from lytic infection of oligodendrocytes by the polyomavirus JC (JCV). Originally, JCV was thought to replicate exclusively in human glial cells, specifically oligodendrocytes. However, we have recently shown that JCV can replicate in cells of lymphoid origin such as hematopoietic precursor cells, B lymphocytes, and tonsillar stromal cells. To determine whether tonsils harbor JCV, we tested a total of 54 tonsils, 38 from children and 16 from adult donors. Nested PCRs with primer sets specific for the viral T protein and regulatory regions were used for the detection of JCV DNA. JCV DNA was detected in 21 of 54 tonsil tissues, or 39% (15 of 38 children and 6 of 16 adults) by using regulatory-region primers and in 19 of 54 tonsil tissues, or 35% (13 of 38 children and 6 of 16 adults) by using the T-protein primers. The DNA extracted from children’s nondissected tonsil tissue, isolated tonsillar lymphocytes, and isolated stromal cells that demonstrated PCR amplification of the JCV regulatory region underwent cloning and nucleotide sequencing. Of the regulatory-region sequences obtained, nearly all contained tandem repeat arrangements. Clones originating from nondissected tonsil tissue and tonsillar lymphocytes were found to have sequences predominantly of the Mad-1 prototype strain, whereas the majority of clones from the DNA of tonsillar stromal cells had sequences characteristic of the Mad-8(br) strain of JCV. A few clones demonstrated structures other than tandem repeats but were isolated only from tonsillar lymphocytes. These data provide the first evidence of the JCV genome in tonsil tissue and suggest that tonsils may serve as an initial site of viral infection.